The Reciprocal Relations Between Female and Male Play Partners and Aggression in Early Childhood. Issue 1 (30th October 2018) - Perry, Kristin J.; Ostrov, Jamie M.
Abstract : This study examined the relations between male and female play partners (PP) and relational (RA) and physical (PA) aggression in an early childhood short‐term longitudinal study ( N = 164, M age = 47.11 months, SD = 7.37 months). A cross‐lagged path analysis was used to examine these relations from Time 1 (T1) to Time 2 (T2), 4 months after T1, and a multiple group analysis was tested across gender. Results showed that T1 male PP predicted an increase in PA, T1 RA predicted an increase in female PP, and T1 PA predicted a decrease in female PP. One path was not equivalent across gender. A post hoc interaction between male and female PP at T1 on future RA was evaluated.